Visible light assisted photodegradation of thimerosal by high performance ZnFe2O4/poly(o-phenylenediamine) composite. (August 2019) - Sandoval, Claudio; Ranganathan, Suresh; Ramírez, Eimmy; Mansilla, Héctor D.; Dinamarca, Robinson; Pecchi, Gina; Yáñez, Jorge
Graphical abstract: Highlights: TMS degradation by visible light driven ZnFe2 O4 /PoPD composite was achieved. ZnFe2 O4 /PoPD photocatalyst was characterized by various techniques. Cleavage of HgS and HgC bond occurs and Hg(II) reduced into Hg(0). As-formed Hg(0) can be removed and easily trapped in copper as amalgam. Photolysis of TMS gives Hg(II), dithiosalicylic acid etc. Abstract: Thimerosal is a mercury-based preservative that is used in pharmaceuticals, vaccines and health-care products. However, thimerosal toxicity has been well explored and hence it should be properly treated for avoiding its occurrence in the environment. Hence, we synthesized visible light active ZnFe2 O4 /poly( o -phenylenediamine) composite as photocatalyst for degradation of thimerosal. The well characterized ZnFe2 O4 and composite effectively degraded thimerosal and subsequently reduced Hg(II) into Hg(0) under visible light irradiation. Thimerosal degradation by-products and generation of Hg(0) were analyzed by high performance liquid chromatography and atomic fluorescence spectroscopy. The composite showed better photocatalytic activity than the pure ZnFe2 O4 nanoparticles. Under the optimum conditions, 90.2% degradation of thimerosal was achieved within 6 h of irradiation. An efficient charge separation ability of poly( o -phenylenediamine) contributes to the high photocatalytic performance of the composite. This work provides a new photocatalytic degradation pathway of thimerosal and thus will stimulate further studies in the removal of organometallic contaminants.